Oil well pipe, oil well pipe threaded joint and coating
By forming a resin film of alkaline soap and adhesive resin on the surface layer of the oil well tube thread, the problem of damage to the solid lubricating film during the tightening process is solved, and the lubricity and rust resistance are improved.
Patent Information
- Application Number
- CN202380060179.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-25
- Filing Date
- 2023-08-14
- Publication Date
- 2025-03-18
AI Technical Summary
During the tightening of the oil well pipe thread, the solid lubricated cover is susceptible to loosening and eccentric swing, resulting in reduced damage and wear resistance, which in turn causes burns and rust prevention problems.
A resin film composed of alkaline soap and adhesive resin is formed on the surface layer of the threaded portion of the oil well tube thread, and the alkaline soap layer is concentrated on the surface side to reduce loose damage and improve lubricity and rust resistance.
By forming an alkaline soap layer, loose damage before thread engagement is reduced, lubricity and rust resistance are improved, and the service life of the threaded joint of the oil well pipe is extended.
Smart Images

Figure CN119654514A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an oil country pipe having lubricity and rust resistance imparted to a threaded portion by a solid lubricating film, an oil country pipe threaded joint using the oil country pipe, and a coating material for forming an outermost layer (top coat) of a threaded portion.
[0002] The coating can be used to repair the lubricating film formed on the threaded portion of the oil well pipe. Background Art
[0003] Oil well pipe threaded joints are generally fastened by applying a viscous lubricant called a compound to form a wet lubricating film on the threaded portion. In addition, the compound contains heavy metals such as Pb and Zn.
[0004] In recent years, environmental pollution has been considered a problem, and as a lubricant for lubricating the threaded portion, a shift to lubricants that do not contain heavy metals is being made. However, as long as a wet lubricant is used, the following problems exist. For example, when used in the desert, if flying sand adheres to the threaded portion of the oil well pipe, there is a risk of burns when tightening the threaded joint. In addition, when used in cold areas, there is a problem that the wet lubricant freezes and is difficult to apply.
[0005] In order to solve these problems, there is a technique of using a dry solid lubricating film that does not contain heavy metals for lubrication of the threaded portion of an oil well pipe. As a technique of using a solid lubricating film for an oil well pipe, there are techniques described in Patent Documents 1 to 3, for example.
[0006] Patent Document 1 discloses a double film consisting of a viscous liquid or semi-solid lubricating film and a dry solid film formed thereon. Patent Document 1 states that, with this structure, the oil well pipe threaded joint not only has rust resistance and burn resistance, but also has the property of being difficult for foreign matter to adhere. In addition, Patent Document 1 states that, as a lubricant, it is necessary to contain at least a fatty acid alkaline earth metal salt. In addition, Patent Document 1 states that, in order to improve the uniform dispersibility of the fatty acid alkaline earth metal salt, a component selected from an organic resin, an oil agent, and an additive can be added.
[0007] In Patent Document 2, a solid lubricating film with a high friction coefficient is formed on a portion of the metal contact portion. In addition, in Patent Document 2, a viscous liquid lubricating film or a solid lubricating film with a low friction coefficient is formed on at least one of the surfaces of the portion other than the contact surface and the contact surface of the counterpart side member. Patent Document 2 states that: With this structure, a large torque resistance on the shoulder is achieved. In Patent Document 2, rosin-based substances, waxes, metal soaps, and alkaline aromatic organic acid metal salts are described as preferred examples of the viscous liquid lubricating film. In addition, in Patent Document 2, metal soaps are defined as salts of fatty acids and metals other than alkali metals. Moreover, Patent Document 2 states that: With this structure, it is effective to improve the anti-burning effect and anti-rust effect of the film.
[0008] Patent Document 3 states that a lubricating film is formed by applying a lubricating film-forming composition to the fitting surface of any one of a sleeve and a pin constituting a threaded joint. The lubricating film-forming composition is formed by dissolving one or more alkaline oils selected from alkaline sulfonates, alkaline salicylates and alkaline phenolates with a dissolving base. Moreover, Patent Document 3 states that good rust resistance and lubricity can be obtained by this structure. In addition, Patent Document 3 states that in order to further improve the burn resistance, a powder of a thermoplastic resin can be contained. In addition, Patent Document 3 states that as a diluting component of the alkaline oil, an alkaline earth metal salt or an alkali metal salt of a fatty acid can be contained.
[0009] Each of the above documents describes a solid lubricating film related to an oil well pipe threaded joint.
[0010] On the other hand, solid lubrication technology in fields other than the field of oil well pipe threaded joints is described in, for example, Patent Documents 4 and 5.
[0011] Patent Document 4 discloses an invention relating to a lubricant used when a metal workpiece is subjected to wire drawing using a die. Patent Document 4 describes the following as advantages of a dry wire drawing lubricant containing an alkali metal soap. That is, as a first advantage, it is described that a film having excellent lubricity can be formed. In addition, as a second advantage, it is described that the lubricant can be easily removed before plating or heat treatment because the film is water-soluble.
[0012] On the other hand, Patent Document 4 lists as a disadvantage of the dry wire drawing lubricant containing alkali metal soap that it liquefies when exposed to high temperature, and the followability and ductility to the wire required by the lubricant are reduced. In response to this, Patent Document 4 records that a certain amount of unsaturated fatty acid metal soap or alkaline soap that is easy to undergo intermolecular polymerization reaction is also added to the metal soap or alkaline soap of saturated fatty acid. This record is a record under the harsh wire drawing processing conditions of high temperature, high pressure and high speed. Moreover, Patent Document 4 records: According to this structure, a dry wire drawing lubricant that also exhibits lubricity, peeling resistance, heat resistance and high temperature ductility under the above-mentioned harsh conditions can be obtained. The lubricant described in Patent Document 4 is made by drying the specified ingredients. Then, the lubricant is crushed into a solid, powder or granular state and then put into a mold box for use.
[0013] In addition, Patent Document 5 discloses an invention related to a steel wire agent having a lubricating film on the surface. Patent Document 5, as one of the prior arts, records that a composite film (chemical conversion treatment film) composed of a zinc phosphate film and a soap layer has high processability and corrosion resistance. On the other hand, Patent Document 5 records that: from the perspective of environmental protection, a lubricating film that does not contain phosphorus has been required in recent years. Moreover, Patent Document 5 records that silicon, tungsten and alkali metal salts of fatty acids are combined in a specified ratio. Patent Document 5 records that: according to this structure, a lubricating film with high processability and corrosion resistance can be obtained even without phosphorus. Here, the alkali metal salt of fatty acid is combined to prevent the friction reduction of the lubricating film and the poor forging appearance. Moreover, it is recorded that: since the alkali metal salt is water-soluble, water evaporates to form a film. Moreover, Patent Document 5 records that: when forming the film, the alkali metal salt is finely and evenly precipitated, it is not easy to produce local wear state differences, and a good forging appearance can be obtained.
[0014] Prior art literature
[0015] Patent Literature
[0016] Patent Document 1: Japanese Patent Application No. 2008-537062
[0017] Patent Document 2: Japanese Patent Application Publication No. 2013-108556
[0018] Patent Document 3: Japanese Patent Application Publication No. 2002-173692
[0019] Patent Document 4: Japanese Patent Application Publication No. 2009-132811
[0020] Patent Document 5: Japanese Patent Application Publication No. 2017-66515 Summary of the invention
[0021] Problems to be solved by the invention
[0022] The inventors have found that, in the actual tightening of oil well pipe threads in wells, it is often observed that the pin threads are rotated by power tongs from a state where the pin threads and the sleeve threads are not fully engaged. In addition, the inventors have found that the wear resistance is reduced in the case of a solid lubricating film by tightening through the following two processes (steps). That is, due to the eccentricity and swing of the oil well pipe in the stage where the threads are not engaged (step 1), the solid lubricating film formed on the threaded portion constituting the threaded joint is damaged. As a result, the phenomenon of reduced wear resistance in the tightening process (step 2) after the threads are engaged was discovered.
[0023] Next, this viewpoint will be supplemented.
[0024] For solid lubricating films, if actual wells are considered, it is necessary to assume that the solid lubricating films are inevitably worn away to a certain extent during tightening and loosening. The inventors have obtained the following knowledge: the worn away fragments have been the root cause of burning failures in the past. Therefore, the inventors have obtained the following knowledge: if the lubricity evaluation of solid lubricating films is not performed under conditions simulating an actual well or close to an actual well, the evaluation will be meaningless in an actual well.
[0025] Here, as a test that has been frequently used in the past, there is a tightening test in a laboratory using only a short pin of about 1 m. In this tightening test, the sample judged as NG regarding the lubrication of the solid lubricating film that is the object of the present invention is also NG in the actual well. However, the present inventors have found that even if the evaluation in the conventional test using the short pin is judged as OK, there is no guarantee that the judgment is OK in the actual well.
[0026] It should be noted that in the case of a viscous liquid lubricating compound, since it is wet, there is not much difference between the tightening and loosening evaluation using a short pin in the laboratory and the actual situation in the well. There is a tendency that the judgment in the actual well is also linked to the evaluation in the laboratory. It is assumed that the viscous liquid lubricating compound is effective for moving in conjunction with tightening during tightening and loosening.
[0027] On the other hand, in the case of a solid lubricating film, the fragments that are inevitably ground off do not necessarily move in conjunction with tightening and loosening. Therefore, in an actual well where the generation of fragments is bound to increase, the fragments are easily clogged. In addition, the following insight was obtained: when peeling occurs significantly, burns occur at the portion where the solid lubricating film becomes thinner or disappears. Based on this insight, the inventors have obtained the following insight: in the evaluation of the solid lubricating film, it is necessary to perform an evaluation based on this.
[0028] This viewpoint will be described in more detail.
[0029] In actual wells, the situation where the actual length of the pin thread is tightened to the sleeve thread is not implemented under the ideal conditions described in textbooks. Under ideal conditions, it is believed that the actual size pin is set upright and embedded relative to the sleeve thread, and it is tightened straight. However, this is not the case in reality. The structure of the oil well pipe thread has an incomplete threaded portion when the pin thread enters the sleeve thread in the form of insertion. During the initial setting, there are many cases where the pin is set slightly tilted by the amount of looseness (clearance, margin) of this portion. Moreover, at the beginning of the tightening of the thread, the pin thread contacts with the amount of clearance. Moreover, before the threads engage with each other, with respect to the solid lubricating film, the weight of the pin (large load) is superimposed on the offset load used to move the pin in an offset manner. Moreover, in any case, the concern that the solid lubricating film is abnormally ground or stripped off without leaving any part becomes high.
[0030] exist Figure 3 , Figure 4 It is specifically shown in FIG.
[0031] Figure 3 , Figure 4 The example shown in the example is an example of a tightening and loosening test condition where the rotation is at 15 to 25 rpm before the torque rises and at 2.5 to 1.5 rpm after the torque rises. This is the result of a test under stricter conditions (faster rotation speed) than the conditions specified in the thread operation instructions (tightening instructions in the technical package). Figure 3 , Figure 4 The example shown in the figure is the use of JFELION for cementing materials and 9-5 / 8” 53.5#Q125 raw materials with strength grade TM An example of evaluating a solid lubricant coating on a thread.
[0032] Figure 3 This is a torque rotation diagram based on the previous laboratory evaluation method using a short pin of about 1m and tightening with a vertical power tong. Since the pin is short, it is not difficult to operate, and the pin can be set straight. By manually tightening, it can be set to a state where the pin thread is almost not exposed ( Figure 3 (b)). In the torque rotation diagram in this case, the torque starts to rise from the start of tightening, exceeds the bending point of the shoulder torque, and tightens. That is, in this case, it is a very common diagram ( Figure 3 (a)). Here, the torque rises immediately because the pin thread and the sleeve thread are fully engaged in the initial setting stage and tightening is performed from the preset position.
[0033] on the other hand, Figure 4This is a torque rotation diagram when using a Range-3, which is a real-size pin of more than 40 feet (more than 12 meters). It is the result of a test in a simulated well. Here, the unit (size) of the horizontal axis is the same as Figure 3 Different. It should be noted that the simulated well is not an actual well that produces oil / gas, but an experimental well in which a hole is opened in a simulated manner by inserting more than three actual-sized pins into the underground direction (downward). It also refers to a device group or experimental facility that has a stand that can be set up with about 2 to about 3 connected pins suspended from its ceiling and can perform tightening and loosening tests. This example is a tendency under the same setting as in an actual well, but it is different from the short pin. Figure 3 In this case, the stable torque did not rise until about 6.3 revolutions, and a spike-like torque was observed to rise irregularly from time to time during the rotation. The following insight was obtained: this phenomenon is directly related to the damage of the solid lubricating film, and it is important to evaluate the solid lubricating film based on this.
[0034] Should Figure 4 The torque diagram occurs when setting Range-3, i.e., a pin of more than 40 feet (more than 12m), and tightening it. In this case, since it is an actual size pin (about more than 12m), the pin cannot be set completely straight, and the pin is almost always inserted slightly tilted. It should be noted that this is the same condition as the actual well situation. Therefore, even if the pin is set by manual tightening, the pin thread and the sleeve thread will partially touch too strongly. Therefore, when the pin thread teeth are more than 5 teeth, about half of the total thread teeth cannot move forward further when exposed from the sleeve during manual tightening. From this state, tightening with pliers is started. Moreover, the threads are almost always not fully engaged with each other, and a part of them accidentally touches strongly, becoming a state that cannot move forward further. Therefore, before the threads of the actual size pin are fully engaged with each other, the sleeve thread and the pin thread touch each other in an offset state. That is, it means that damage is caused to each other. On this basis, the following findings were obtained: if the solid lubricating film is not evaluated, as described above, a sample that is NG in the evaluation using a short pin alone is NG in the actual well, but a sample that is OK in the evaluation using a short pin does not necessarily mean that it is OK in the actual well. Therefore, the following findings were obtained: in the upper and lower limit regulations of parameters such as components and conditions in the previous inventions, the regulations evaluated based on OK in the evaluation of the short pin are not necessarily a good range in the actual well.
[0035] Patent Documents 1 to 3 are all documents related to solid lubrication technology for oil well pipe threaded joints. However, Patent Documents 1 to 3 assume that short pins are used for test evaluation. Therefore, in Patent Documents 1 to 3, there is still room for improvement in order to reduce the damage to the solid lubricating film in step 1.
[0036] On the other hand, Patent Documents 4 and 5 are methods of using solid lubricants in technical fields other than the oil well pipe field, and relate to lubrication applications in plastic working of metals. That is, Patent Documents 4 and 5 do not describe any conversion to the oil well pipe field.
[0037] Here, in Patent Document 4, metal soap or alkaline soap is used as a solid lubricant. However, in the technology of Patent Document 4, it is assumed that the lubricant is in a solid, powdery or granular form and is placed in a use environment where the lubricant is dried. Therefore, the technology of Patent Document 4 is not intended to be used for oil well pipe threads at all. For example, even if the solid lubricant described in Patent Document 4 is applied to a vertically erected oil well pipe thread, the solid lubricant will fall and cannot be retained on the surface of the threaded portion.
[0038] In addition, in Patent Document 5, a lubricating film containing alkaline soap is formed on the surface of the steel material after a predetermined reagent is applied to the steel material and water as a solvent is evaporated. However, when this method is applied to the tightening operation of the threads of oil well pipes, the following problem occurs. That is, the water-soluble alkaline soap provided on the threaded portion of the oil well pipe is easily washed away by rainfall and the backflow of muddy water from the well. As a result, in the field of oil well pipes, lubricity cannot be maintained by the method described in Patent Document 5.
[0039] In addition, oil well pipe threads are required to have strong corrosion resistance that does not rust even after years of outdoor storage. However, it is generally believed that alkaline soaps will introduce water due to their deliquescent properties, and are therefore generally not preferred from the perspective of corrosion resistance. However, the reality is that rust resistance is not required in Patent Document 4. In addition, in Patent Document 5, only rust resistance that can withstand indoor storage for only two months is required.
[0040] The present invention has been made in view of the above-mentioned aspects, and an object of the present invention is to provide an oil well pipe threaded joint having a solid lubricating film having excellent lubricity and rust prevention properties.
[0041] Methods used to solve problems
[0042] As described by the inventors above, in the tightening of the oil well pipe threaded joint, looseness, that is, eccentricity and swing of the oil well pipe occurs at the stage where the threads of the pin and the sleeve are not engaged (step 1). Due to the occurrence of this looseness, the solid lubricating film formed on the thread is damaged. The inventors have found that in order to suppress this damage, it is effective to directly form an alkaline soap layer on the thread surface of at least one of the pin or the sleeve, or to form an alkaline soap layer on the solid lubricating film.
[0043] Here, the alkaline soap in the present invention refers to a salt composed of a fatty acid and an alkali metal such as sodium or potassium. The alkaline soap in the present invention is distinguished from a metal soap which is a salt of a fatty acid and a metal other than an alkali metal.
[0044] In the past, when soap was used as a solid lubricant for oil well pipe threaded joints, metal soap was used, and alkaline soap was not paid attention to. This is because, as mentioned above, alkaline soap is water-soluble and has poor water resistance and rust resistance. In addition, metal soap is easier to disperse in general binder resins.
[0045] However, the present inventors have found that intentionally adding an alkaline soap to a solvent in which the resin is dissolved can form an alkaline soap layer on the surface of the resin film, which is effective in reducing the looseness. The present inventors have completed the present invention based on this finding.
[0046] Furthermore, in order to solve the problem, one embodiment of the present invention is directed to an oil well pipe constituting the sleeve or the pin used for an oil well pipe threaded joint in which a sleeve having an internal thread and a pin having an external thread are connected, wherein the outermost layer of the threaded portion has a resin film containing an alkaline soap as a solid lubricant in a binder resin, and the resin film has an alkaline soap layer formed on the surface.
[0047] Another aspect of the present invention is directed to an oil country tubular good threaded joint in which a sleeve having an internal thread and a pin having an external thread are connected, wherein at least one of the sleeve and the pin is formed of the oil country tubular good of one aspect of the present invention.
[0048] Effects of the Invention
[0049] According to one embodiment of the present invention, a resin layer in which alkaline soap is dispersed is formed on the surface side as the outermost layer of the threaded portion of an oil country pipe, thereby providing an oil country pipe threaded joint having a solid lubricating film excellent in lubricity and rust resistance with a simple structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 It is a figure which shows an oil country pipe and an oil country pipe threaded joint.
[0051] Figure 2 It is a cross-sectional view showing a configuration example of a lubricating film formed on a threaded portion.
[0052] Figure 3 , (a) is an example of a tightening diagram in a conventional laboratory test, and (b) is a diagram showing an example of an initial setting position at that time.
[0053] Figure 4 In the figure, (a) is an example of a tightening diagram in an actual well, and (b) is a diagram showing an example of an initial setting position at that time.
[0054] Figure 5 Schematic diagram of the tightening diagram, where (a) is the actual well situation and (b) is the situation of the previous laboratory test.
[0055] Figure 6 is a diagram illustrating the conditions of the new laboratory test (weight clamp).
[0056] Figure 7 It is a figure which shows the installation example of the weight in the condition (weight clamp) of a new laboratory test. DETAILED DESCRIPTION
[0057] Next, embodiments of the present invention will be described with reference to the drawings.
[0058] The present invention relates to a film structure formed on a fastening surface in a threaded portion of an oil well pipe used for oil / gas, and an oil well pipe threaded joint having the film structure as a lubricating film. One of the features of this embodiment is a solid lubricating film formed on the fastening surface of the threaded joint.
[0059] However, the present invention does not particularly limit the structure of the threaded joint itself. The structure of the threaded joint can adopt a known or new structure.
[0060] <Oil well pipe and oil well pipe threaded joint>
[0061] Oil well pipes, for example, Figure 1 The coupling shown is composed of a sleeve 2 and a pin 1.
[0062] like Figure 1 As shown, the oil well pipe threaded joint is composed of a sleeve 2 such as a coupling having an internal thread 2a and a pin 1 having an external thread 1a.
[0063] In the present embodiment, a resin film according to the present invention is formed on the outermost surface of the contact surface (fastening surface) of the threaded portion of at least one of the sleeve 2 and the pin 1 (see Figure 2 ).
[0064] Here, the resin film 31 of this embodiment constitutes the outermost film when the lubricating film is composed of multiple layers with respect to the threaded portion. Figure 2 As shown, when the lubricating film has a multilayer film structure, the resin film 31 of this embodiment is not applied to the film inside the outermost layer (see Figure 2 (a)). Figure 2 In (a), reference numeral 30 denotes another solid lubricating film, a base layer, etc. formed in a layer below the resin film 31. A plurality of lubricating films may be provided in a layer below the resin film 31.
[0065] The main purpose of forming the resin film 31 of the present invention is to reduce the looseness in the above-mentioned step 1. It is assumed that the lubricity in step 2 depends on another solid lubricating film. Therefore, in this embodiment, it is assumed that another solid lubricating film is formed on the other side or both sides of the pin thread or the sleeve thread. And, for example, the resin film 31 of the present invention is formed on any other solid lubricating film among the formed other solid lubricating films.
[0066] Alternatively, when another solid lubricating film is formed on only one of the pin thread or the box thread, the resin film 31 of the present invention is formed on the thread surface of the other thread on which the other solid lubricating film is not formed.
[0067] However, the resin film 31 of the present invention can also be directly formed on the surface of the threaded portion of the oil well pipe and effectively used only as a rust-proof film for the pin thread and the sleeve thread. In addition, the resin film 31 of the present invention can also be formed as a top coat by applying a coating material for repairing or surface protection.
[0068] <Paint>
[0069] The coating material for forming the resin film 31 of the present embodiment is composed of a coating material obtained by dissolving an alkaline soap as a solid lubricant and a binder resin in an organic solvent. The coating material is applied to the threaded portion constituting the oil well pipe threaded joint. Then, the coating liquid is dried while being heated as necessary, thereby obtaining the resin film 31.
[0070] <Organic solvents>
[0071] As the organic solvent, an organic solvent other than lower alcohol (having 5 or less carbon atoms) is selected. This is because if a lower alcohol is selected, the affinity with the binder resin described later is poor and a homogeneous resin film 31 cannot be formed.
[0072] The type of organic solvent used is not limited as long as it is not a lower alcohol. However, if high productivity is required for coating on oil well pipe thread manufacturing lines and coating in oil well pipe tightening operations in wells, the organic solvent used is preferably a quick-drying, highly volatile solvent. Specifically, the organic solvent used is preferably a material with a boiling point of 60°C or less.
[0073] Furthermore, a higher flash point is more preferable when considering safety in the well during formation of the resin film 31. Specifically, the organic solvent used is preferably a material having a flash point of 60°C or higher.
[0074] As the solvent satisfying these conditions, fluorine-based solvents can be cited. As such fluorine-based solvents, so-called freon substitutes, ie, HFC (hydrofluorocarbon), HFE (hydrofluoroether), HFO (hydrofluoroolefin), PFC (perfluorocarbon) and the like can be cited.
[0075] <Binder resin>
[0076] The binder resin plays a role in holding the alkaline soap functioning as a solid lubricant on the threads of the oil well pipe. Therefore, even if the oil well pipe is vertically erected or in contact with running water, the alkaline soap contained in the formed resin film 31 will not be lost.
[0077] Furthermore, when dissolving or dispersing the solid lubricant in the binder resin, it is generally desired to dissolve or disperse the solid lubricant uniformly. Therefore, as the binder resin, a material having a high affinity for the solid lubricant, that is, a material having a close SP value, is generally selected.
[0078] In contrast, in this embodiment, a binder resin with low compatibility with alkaline soap is intentionally selected so that when the coating is applied, the alkaline soap is concentrated on the surface side, i.e., the alkaline soap automatically floats on the surface side, thereby forming an alkaline soap layer 31A with a high lubricating effect on the film surface.
[0079] From this viewpoint, in the present embodiment, as the binder resin, a resin having an SP value of 10.0 cal / cm 3 The following binder resins.
[0080] Here, the binder resin includes not only a single resin but also a composite resin. Even for the same resin, the SP value varies depending on the molecular weight, type and number of functional groups. Therefore, it is not possible to generalize which resin satisfies the above SP value. As resins with relatively low SP values, fluororesins, polyethylene, etc. can be listed.
[0081] In addition, the SP value of the binder resin was set to 10.0 cal / cm 3 The following will also improve the hydrophobicity and water resistance of the resin itself, thereby improving its rust resistance.
[0082] In addition, the higher the water repellency of the binder resin, the more preferable it is.
[0083] On the contrary, the SP value of the binder resin is greater than 10.0 cal / cm 3 When the rust resistance of the resin itself is reduced, the alkaline soap having deliquescent properties is easily dispersed in the resin below the alkaline soap layer 31A. As a result, the binder resin cannot obtain sufficient rust resistance.
[0084] Here, the lower limit of the SP value of the binder resin is not particularly limited, but is set to be 5.0 or more, for example.
[0085] Here, regarding the calculation of the SP value, when the molecular structure is known, the Fedors method may be used, and when the molecular structure is unknown, the turbidity titration method may be used.
[0086] In addition, the binder resin preferably has an average molecular weight of 10,000 to 300,000. When the average molecular weight is lower than 10,000, the affinity with the alkaline soap becomes high, and it is difficult to obtain an alkaline soap layer 31A that is stable with respect to the surface layer. On the other hand, when the average molecular weight is higher than 300,000, the hardness of the resin increases, and it is difficult to uniformly apply the coating to the thread surface, and there is a possibility that the lubricating effect of the alkaline soap in the above step 1 is impaired.
[0087] <Alkaline soap>
[0088] In the present embodiment, alkaline soap is used as the solid lubricant.
[0089] In the present invention, the alkaline soap refers to a salt composed of a fatty acid and an alkali metal such as sodium or potassium. That is, the alkaline soap in the present specification does not include a metal soap that is a salt of a metal other than a fatty acid and an alkali metal.
[0090] The type of fatty acid constituting the alkaline soap is not particularly limited. Representative examples of fatty acids include stearic acid, palmitic acid, myristic acid, lauric acid, behenic acid, caprylic acid, oleic acid, linoleic acid, linolenic acid, ricinoleic acid, and 12-hydroxystearic acid.
[0091] In the present invention, the alkali metals constituting the alkaline soap are substantially only sodium and potassium.
[0092] Although there are other alkali metals, they are generally not marketed in the form of alkaline soaps, or, like lithium, are substances with properties similar to alkaline earth metals (as salts with fatty acids, metal soaps). These alkali metals are not included in the alkali metals constituting the alkaline soap in this specification. That is, although there are lithium, rubidium, and cesium among the alkali metals, these alkali metal salts are not included in the soap (alkaline soap) of the present invention.
[0093] In reality, alkaline soaps of rubidium and cesium are almost not circulated, so they are not practical. In addition, lithium soaps are used as thickeners mixed in grease, unlike sodium and potassium, which are used for cleaning, so they are not used for lubrication purposes.
[0094] The weight of the alkaline soap is preferably 0.01 times or more and 3 times or less the weight of the binder resin.
[0095] The resin film 31 of the present embodiment exhibits higher lubricity than other lubricants by concentrating the alkaline soap on the surface layer of the resin film 31 , thereby reducing film damage caused by looseness before meshing of oil country pipe threads.
[0096] In order to exert this effect, the alkaline soap is preferably added in an amount of at least 0.01 times the weight of the binder resin. On the other hand, when the alkaline soap is too much, it is possible to hinder the formation of a homogeneous resin film 31, and the rust resistance is deteriorated. Therefore, the alkaline soap can be added up to 3 times the weight of the binder resin as the upper limit. It should be noted that the more preferred weight of the alkaline soap is more than 0.1 times and less than 2 times the weight of the binder resin.
[0097] <Other additives>
[0098] The coating material forming the resin film 31 of the present embodiment may contain additives other than the alkaline soap for the purpose of improving lubricity, rust resistance, and the like.
[0099] For example, by adding PTFE, metal soap, graphite, etc. as other solid lubricants, the wear resistance after the oil well pipe is threaded can be improved. In this case, as the other solid lubricant, a solid lubricant with a lower SP value than the alkaline soap or a solid lubricant with a heavier mass than the alkaline soap is used, and it is preferred to use a solid lubricant in which the other solid lubricant is not concentrated on the surface side of the resin film 31.
[0100] Alternatively, zinc phosphate or aluminum phosphate may be added as a rust inhibitor to further improve corrosion resistance during long-term storage.
[0101] <Coating method>
[0102] The coating method of the present embodiment to the threaded portion of the oil well pipe is not particularly limited. As the coating method, for example, spraying, brush coating, dipping, etc. can be cited. In order to form a uniform film, spraying is preferred. In addition, the oil well pipe can be rotated at a constant speed during coating and drying.
[0103] In this way, the resin film 31 according to the present invention can be formed.
[0104] Regarding the resin film 31, Figure 2 In this way, the alkaline soap is concentrated on the surface side, and as Figure 2 In this way, an alkaline soap layer 31A is formed on the surface.
[0105] In the present embodiment, “the alkaline soap is concentrated on the surface side” means that 70% by weight or more of the alkaline soap contained in the resin film 31 is located on the upper half side (surface side) of the resin film 31. Preferably, 90% by weight or more is located on the upper half side (surface side) of the resin film 31. In this way, the alkaline soap layer 31A can be formed by dispersing the alkaline soap contained in the binder resin on the surface side.
[0106] As a method for concentrating the alkaline soap on the surface side, in addition to adjusting the SP value of the binder resin, the coated oil country pipe can be rotated at a constant speed during the application of the coating material for the resin film 31 and during the drying of the coating material. In order to obtain a stable alkaline soap layer 31A, natural drying is more preferable than forced drying.
[0107] It should be noted that the concentration of alkaline soap on the surface side can be confirmed, for example, by quantification of the alkali metal in the alkaline soap using EDX (energy dispersive X-ray analysis). This confirmation can be confirmed by the distribution of the alkaline soap in the film thickness direction. This confirmation is carried out, for example, by cutting out any film thickness section in the threaded portion after the film is formed and using EDX to measure the concentration of the alkali metal (sodium or calcium) at equal intervals in the film thickness direction. In addition, this confirmation is determined, for example, by calculating the average concentration of the upper half of the film thickness relative to the average concentration of the entire film thickness.
[0108] <Hardness of the resin film 31>
[0109] The resin film 31 formed by the above method is preferably soft with a pencil hardness of not more than F. The hardness of the resin film 31 is mainly determined by the binder resin.
[0110] It is considered that by making such a soft resin film 31, the film is appropriately ground off at the stage where looseness occurs before the oil country pipe is threadedly engaged, and the lubricity of the alkaline soap layer 31A is exerted.
[0111] The pencil hardness of the resin film 31 is more preferably 3B or less. The pencil hardness of the resin film 31 may be 6B or less.
[0112] On the contrary, when the pencil hardness of the resin film 31 is too high, the looseness reduction effect may not be obtained. In addition, the resin film 31 peeled off by the tightening of the thread may not be finely divided, resulting in the risk of clogging and further abrasion.
[0113] Here, the pencil hardness is measured in accordance with the provisions of JIS K 5600-5-4. The pencil hardness of the resin film 31 can be adjusted mainly by changing the average molecular weight of the binder resin.
[0114] <Thickness of the resin film 31>
[0115] The film thickness of the formed resin film 31 is preferably in the range of 3 μm or more and 50 μm or less. If the film thickness is too thin compared to 3 μm, sufficient lubricity and rust resistance cannot be obtained. On the other hand, if the film thickness is too thick compared to 50 μm, excessive cutting slag is generated during thread tightening, which may cause thread burning.
[0116] (Function and others)
[0117] As mentioned above, the lubrication behavior of oil well pipe threads can be roughly divided into the following two steps.
[0118] Step 1: It is the stage from inserting the pin thread into the sleeve thread to the thread engagement. This is equivalent to Figure 4 (a) There is an initial oscillation in step 1 Figure 5 (x) region of (a).
[0119] Step 2: This is the stage where the threads are tightly tightened after they are meshed and in strong contact with each other.
[0120] In the loosening process, on the contrary, it can be roughly divided into a stage where the threads start to loosen from the stage where they are in strong contact with each other and the engagement of the threads ends (step 2), and a stage where the pin thread and the sleeve thread are not strongly engaged with each other and have a clearance (looseness) and thus loosen (step 1).
[0121] Furthermore, when tightening the oil well pipe threaded joint, looseness, that is, eccentricity and swing of the oil well pipe occurs at the stage (step 1) when the threads of the pin and the sleeve are not engaged. Due to the occurrence of this looseness, the solid lubricating film formed on the thread is damaged.
[0122] In this regard, in the present embodiment, in order to suppress such damage, a resin film 31 having an alkaline soap layer 31A on the surface is directly formed on the thread surface of at least one of the pin and the sleeve, or a resin film 31 having an alkaline soap layer 31A on the surface is formed on the solid lubricating film. Moreover, the alkaline soap layer 31A suppresses the damage of the solid lubricating film at the stage (step 1) when the threads of the pin and the sleeve are not engaged. That is, in the present invention, when there is "play" before the thread engagement in step 1, the alkaline soap on the surface of the resin film 31 ensures "lubrication" such as "slipping" into a stable position of the thread. That is, when the alkaline soap is tightened in a state where there is shaking in the initial stage of tightening the oil well pipe thread, it supports the lubrication such as sliding into a position close to the original thread engagement position, thereby having the effect of improving the overall lubrication.
[0123] Furthermore, when tightening in a region where there is initial thread play, if the other solid lubricating film 30 formed on both threads or a single thread is not damaged, the original capability of the lubricating property can be directly exerted. As a result, the number of tightening and loosening cycles can be stabilized.
[0124] Here, in the past, metal soaps were used as solid lubricants for oil well pipe threaded joints, and alkaline soaps were not paid much attention. This is because alkaline soaps are water-soluble and have poor water resistance and rust resistance. In addition, metal soaps are more easily dispersed in general binder resins.
[0125] In contrast, in the present embodiment, it was found that by intentionally adding alkaline soap to the solvent in which the resin is dissolved, an alkaline soap layer 31A can be formed on the surface layer of the resin film 31, which is effective in reducing the above-mentioned looseness. This effect is particularly effective when the weight of the alkaline soap contained in the resin film 31 is 0.01 times or more and 3 times or less of the weight of the resin constituting the resin film 31.
[0126] Thus, in the tightening step (step 2) after the screw engagement, the other solid lubricating film 30 can exhibit sufficient wear resistance.
[0127] On the other hand, even if metal soap is added to the solvent in which the resin is dissolved instead of the alkaline soap, a stable metal soap layer is not formed on the surface of the resin film, and the effect of reducing looseness is limited. In addition, the binder resin functions as a binder relative to the alkaline soap. Therefore, after the coating is applied, even if the oil well pipe is vertically erected or even if the oil well pipe is exposed to rainfall or muddy water backflow, it is possible to suppress the alkaline soap layer 31A from peeling off or running off.
[0128] In addition, by selecting the SP value to be 10.0 cal / cm 3 The following resins are used as the binder resins, which can not only form a stable alkaline soap layer 31A on the surface of the resin film, but also obtain the rust resistance required for oil well pipes. Here, when the SP value of the binder resin is too high, the affinity of the resin with the alkaline soap and water becomes high, and the alkaline soap is also dispersed in the resin film. In this case, the deliquescent property of the film as a whole becomes high, inducing rust.
[0129] In addition, the present inventors have found that when the resin film 31 is too hard, that is, when the pencil hardness exceeds F, even if alkaline soap is added, the above-mentioned loosening suppression effect may not be sufficiently obtained. This is presumably because the binder resin supporting the alkaline soap layer 31A becomes too strong, hindering the sliding of the alkaline soap layer 31A. Alternatively, it may be because the polymers in the resin are strongly entangled with each other, so that the alkaline soap molecules are difficult to move to the surface layer, and a stable alkaline soap layer 31A cannot be obtained.
[0130] (Other uses)
[0131] As described above, the resin film 31 of the embodiment can be formed by applying a coating obtained by dissolving an alkaline soap and a binder resin in an organic solvent and drying it. Therefore, the film formation of the resin film 31 is very easy. Therefore, in the case where the formed resin film 31 or another lubricating film is damaged, a repair treatment of applying the coating of the present embodiment and drying it can be performed on the damaged part. In this case, the film can also be repaired, and the lubricity and corrosion resistance can be repaired.
[0132] (other)
[0133] The present invention may also take the following configurations.
[0134] (1) An oil well pipe, which is used in an oil well pipe threaded joint formed by connecting a sleeve having an internal thread and a pin having an external thread, and which constitutes the sleeve or the pin, wherein:
[0135] The outermost layer of the threaded portion has a resin coating containing an alkaline soap as a solid lubricant in a binder resin.
[0136] The resin film has an alkaline soap layer formed on the surface.
[0137] (2) The alkaline soap contained in the resin film is concentrated on the surface side to form the alkaline soap layer.
[0138] (3) The SP value of the above binder resin is 10.0 cal / cm 3 the following.
[0139] (4) The weight of the alkaline soap is 0.01 to 3 times the weight of the binder resin.
[0140] (5) The pencil hardness of the resin film is F or less.
[0141] (6) A separate solid lubricating film is provided as a lower layer of the above-mentioned resin film.
[0142] (7) An oil well pipe threaded joint, which is a threaded joint for oil well pipes formed by connecting a sleeve having an internal thread and a pin having an external thread, wherein:
[0143] At least one of the sleeve and the pin is formed of the oil country tubular good of the present invention.
[0144] (8) A coating material for forming an outermost layer on a threaded portion of an oil well pipe, wherein:
[0145] Contains solvent, binder resin and solid lubricant,
[0146] As the solid lubricant, an alkaline soap is included.
[0147] The SP value of the above binder resin is 10.0 cal / cm 3 The average molecular weight is 10000 or more and 300000 or less,
[0148] The weight of the alkaline soap is 0.01 to 3 times the weight of the binder resin.
[0149] Example
[0150] Next, examples based on this embodiment will be described.
[0151] (About laboratory test methods)
[0152] Conventional laboratory test conditions generally use a method using a vertical power tong using a short pin of about 1 m in length. In addition, conventionally, the test start position is set as the position where the clamp cannot be tightened any further by hand.
[0153] In contrast, in the following embodiments, new laboratory test conditions are adopted, a weight is placed on the upper part of a short pin of about 1m in length, and a tightening and loosening test is performed using a vertical power tong. As a weight, a weight with the weight of 1 to 3 pins in an actual well is used. The reasons are as follows. The environment that occurs in the actual well that is the target of the present invention means that in the example where the short pin is used, the evaluation results are almost all qualified, and it is impossible to truly screen for qualified / unqualified. This is because it often happens that it becomes NG when used in the well even under the conditions of qualified judgment.
[0154] Although repeated, in the present invention, as described above (for example, referring to Figure 2 ), the phenomenon caused by lubrication of oil well pipe threads is considered to be the following two. That is, the inventors have found that it is important to evaluate thread lubrication, including the initial stage (step 1) of tightening and loosening (lubrication) and the second stage (step 2) of lubrication. If the evaluation is performed without considering these two stages, it is likely that although the laboratory evaluation is OK, failures will frequently occur in actual wells.
[0155] Under the conditions of the new laboratory test, the two-stage lubrication that may occur in an actual well can be simulated for evaluation, and the meanings of the upper and lower limits specified in the present invention can be clarified.
[0156] Two-stage lubrication means Figure 5There are two steps: stage (x) of (a) (step 1) and stage (y) + (z) (step 2). In actual wells, the initial setting is not tightened to the level where the threads are fully engaged, and high-speed tightening of about 5rpm to about 20rpm is performed using a power tong. Due to the large load of the entire length of the pin (40 feet ≈ 12m) on the sleeve thread, and because the threads are not engaged with each other, there is looseness. In addition, sometimes the pin thread and the sleeve thread partially touch each other, causing a lot of damage to the solid lubricating film. This is the stage of step 1. If there is a clear torque increase, the tightening speed can be reduced to about 0.5rpm to about 3rpm depending on the type of thread to implement tightening, and tighten until it is fully tightened. This is step 2. Relaxation follows the opposite process.
[0157] Reference Figure 6 and Figure 7 A test apparatus simulating an actual well for carrying out conditions for new laboratory tests will be described.
[0158] The new laboratory test conditions are based on the evaluation under conditions that can achieve large loads during tightening and partial load conditions during loosening. For example, in the case of a large load equivalent to that of a full-size pin and a process in which the threads are tightened continuously, the play before the threads mesh with each other is taken into account. In addition, in the case of a process in which the threads are loosened, the play caused by the disengagement of the threads is reflected.
[0159] Under the conditions of the new laboratory test, such as Figure 6 In this way, a vertical power tong 4 is used. In addition, as a test pin, a short pin 1 is used. However, the load of the weight 3 can be applied to the upper part of the pin 1 and the load can be unloaded.
[0160] Furthermore, the short pin 1 and the sleeve 2 are fastened by the pin thread 1 a and the sleeve thread 2 a.
[0161] At this time, in order to simulate the condition where the threads are not engaged, the initial pre-tightening position is set so that the pin thread 1a appears to be exposed from the sleeve thread 2a by half of the total number of threads (refer to Figure 4 (b)) is set. This is one of the causes of shaking. Start tightening from this state.
[0162] In addition, during tightening, a weight 3 is preliminarily attached to the end portion of the pin 1 on the opposite side of the tightening thread with respect to the sleeve thread 2a.
[0163] The weight of the weight 3 is set to be a load equivalent to one to three pins of actual size, and a weight calculated based on the outer diameter and wall thickness of the pins of actual size is placed.
[0164] like Figure 7 As shown, Figure 6The weight 3 illustrated in the figure is composed of a weight body 3A and an insertion rod 13. The insertion rod 13 is joined to the lower surface of the weight body 3A by welding and is arranged at an axisymmetric position of the weight 3. The weight is attached to the pin 1 by inserting the insertion rod 13 in a loose state. The symbol 1c represents the inner diameter surface of the pin 1.
[0165] When the weight 3 is installed in advance on the insertion rod 13 and the pin 1 as described above, holes 1d and 13a are opened in advance to penetrate the pin 1 and the insertion rod 13. Figure 7 As shown, by inserting the through rod 12 into the holes 1d and 13a, the weight 3 and the pin 1 are integrated.
[0166] A swivel hook 11 is fixed to the center of the shaft of the upper part of the weight 3 by welding, and is formed into a structure of a suspension device 20 suspended from the ceiling by a suspension chain 21. Thus, by adjusting the lifting condition of the weight by the suspension device 20, the load of the weight on the pin can be adjusted.
[0167] When tightening, the chain 21 is set to a relaxed state, a weight load is applied to the sleeve thread, and tightening is performed at 5 to 20 rpm until the torque increases (step 1). This is a simulation of shaking. If the torque increases, the rotation speed is reduced to 0.5 to 2 rpm, and tightening is performed until the tightening position is reached (step 2).
[0168] On the other hand, when loosening (relaxing), the weight 3 is suspended by the suspension device 20, and the loosening is carried out without applying a load to the weight 3. Regarding the rotation speed, when the torque increases, loosening starts at a rotation speed of 0.5 to 2 rpm. Then, when the torque reaches about 1 / 10 of the tightening torque value, loosening is carried out at a high speed of 5 to 20 rpm.
[0169] This enables laboratory testing to be performed under conditions close to those in an actual well.
[0170] (About oil well pipe threaded joints)
[0171] As oil well pipes, pipe bodies (pins) with an outer diameter of 244.48 mm, a wall thickness of 13.84 mm, and a steel grade of API5CT Q125 and corresponding couplings (sleeves) were prepared. As threaded joints, high-quality oil well pipe joints with a pitch of 5.08 mm were used.
[0172] In addition, the resin film 31 according to the present invention or the resin film 31 of the comparative example was formed on the pin thread. A solid lubricating film mainly composed of PTFE, which is different from the resin film 31 of the present invention, was formed on the sleeve thread.
[0173] Then, a tightening and loosening test was performed under the conditions of the new laboratory test to evaluate the wear resistance. At this time, manual tightening was stopped when the pin thread protruded 8 threads from the sleeve, and a weight of 3 tons (the weight of about 3 12m pipes of the same size) was placed on the pin thread pipe, thereby intentionally causing loosening in step 1.
[0174] (Evaluation: Tightening and loosening times)
[0175] Each threaded joint was evaluated based on the number of times it could be tightened and loosened without causing wear to an irreparable level, and was considered acceptable if the number of tightening and loosening was 5 or more.
[0176] If the API5C5 standard is used, the semi-manual tightening and heavy hammer application mentioned above are not required. If the oil well pipe size used in this embodiment can be tightened and loosened three times without wear, it is qualified. However, in order to pursue higher wear resistance, the qualified level is made stricter. It should be noted that when the number of tightening and loosening reaches 10 times, it will stop regardless of whether there is wear or not.
[0177] (Evaluation: Rust resistance)
[0178] Separately from the above test, cut samples of the pin threaded portion of a pipe body having an outer diameter of 88.90 mm, a wall thickness of 6.45 mm, and a steel grade of API5CT L80 were prepared.
[0179] As the pin thread, a high-quality joint for oil country pipes having a pitch of 4.23 mm was used, and the resin film 31 of the present invention or the resin film 31 of a comparative example was formed on the thread surface to produce various samples.
[0180] These were subjected to a salt spray test specified in JIS K 5600-7-1 for 8 hours to confirm the presence or absence of rust, thereby evaluating the rust-proof property.
[0181] Here, no rust is rated as 5 points, rust (area ratio 1% or less) is rated as 4 points, rust (area ratio greater than 1% and less than 10%) is rated as 3 points, rust (area ratio greater than 10% and less than 50%) is rated as 2 points, rust (area ratio greater than 50%) is rated as 1 point, and 4 points or more are considered qualified.
[0182] Table 1 shows the test conditions and evaluation results.
[0183]
[0184] In Table 1, P / B represents the weight ratio of the solid lubricant (alkaline soap) to the binder resin.
[0185] In addition, the main difference between the saturated polyester A and the saturated polyester B described in Table 1 is the hydroxyl value. That is, as the saturated polyester A, a saturated polyester with a hydroxyl value of 10 [KOHmg / g] or less is used. In addition, as the saturated polyester B, a saturated polyester with a hydroxyl value of about 100 [KOHmg / g] is used.
[0186] In addition, as the fluororesin A, a fluororesin having an average molecular weight of about 30,000 was used, and as the fluororesin B, a fluororesin having an average molecular weight of about 200,000 was used.
[0187] As shown in Table 1, HFO, toluene or MEK was used as the organic solvent.
[0188] (Comparative Example 1)
[0189] Comparative Example 1 has an SP value of 10.0 cal / cm 3 The following is a resin film 31. However, this is an example in which the resin film 31 does not contain alkaline soap. Evaluation was performed based on the conditions of this comparative example 1.
[0190] The pencil hardness of the resin film 31 of Comparative Example 1 was B. In Comparative Example 1, the rust resistance was 5 points, which was not a problem, but the number of tightening and loosening was 2 times, which was unacceptable.
[0191] (Examples 1 to 4)
[0192] Examples 1 to 4 are tests for confirming the influence of the concentration of sodium stearate as the alkaline soap contained in the resin film 31. In Examples 1 to 4, the pencil hardness was B or 2B.
[0193] As can be seen from Examples 1 to 4, when the P / B value, which represents the ratio of the weight of the solid lubricant to the weight of the binder resin, is in the range of 0.01 to 3, the number of tightening and loosening times is judged as acceptable.
[0194] Here, even a small amount of alkaline soap can improve the wear resistance. However, it is known that in order to obtain a higher effect, the amount of alkaline soap added can be increased. This is because the lubricity of the alkaline soap reduces the damage to the solid lubricating film on the thread caused by the loosening in step 1.
[0195] On the other hand, it is also known that the rust prevention property slightly decreases when the P / B value is increased to 3. This is considered to be because too much additive makes it difficult to form a dense and homogeneous resin film 31.
[0196] From these results, it is understood that the P / B value may be 0.01 or more and 3 or less. The P / B value is preferably 0.1 or more and 2 or less, and more preferably 0.5 or more and 1.4 or less.
[0197] In view of the above, P / B=1 is set in the following Examples and Comparative Examples.
[0198] (Comparative Example 2)
[0199] Comparative Example 2 is a test in which a metal soap, more specifically, Ca stearate was added instead of the alkaline soap.
[0200] The pencil hardness of Comparative Example 2 was 2B, which was the same as that of Example 3.
[0201] However, although the rust resistance of Comparative Example 2 was 5 points and there was no problem, the number of tightening and loosening was 4 times. That is, the wear resistance of Comparative Example 2 was greatly reduced compared with Example 3 to which alkaline soap (Na stearate) was added. This is because Ca stearate was dispersed in the resin film 31 and did not form a stable soap layer on the film surface like Na stearate.
[0202] (Example 5)
[0203] Example 5 is an example in which a binder resin different from that of Examples 1 to 4 was selected. Specifically, a binder resin with a lower SP value (7.6 cal / cm 3 ), a fluororesin with a slightly higher pencil hardness (F). As a result, the number of tightening and loosening times and the rust resistance were the highest as in Example 3.
[0204] (Comparative Examples 3 and 4)
[0205] Comparative Examples 3 and 4 are examples in which the SP value of the binder resin is high.
[0206] In Comparative Example 3, a saturated polyester resin different from that of Examples 1 to 4 was used. In Comparative Example 4, nitrocellulose was used. In addition, the SP value of Comparative Example 3 was 11.9 cal / cm 3 The SP value of Comparative Example 4 is 13.0 cal / cm 3 .
[0207] It can be seen that although the number of tightening and loosening times of Comparative Examples 3 and 4 both satisfy the acceptance criteria, they are inferior to Example 3 which has the same P / B value and a low SP value.
[0208] In addition, the rust resistance of Comparative Examples 3 and 4 was 3 points and 2 points, respectively, which were unacceptable.
[0209] It can be seen from this that when the SP value of the binder resin is too high, both the wear resistance and the rust resistance are reduced. By comparing with the examples, it can be estimated that the SP value is about 10.0 cal / cm 3 Good wear resistance and rust resistance can be obtained when the above ratio is less than 0.05.
[0210] It should be noted that, regarding Comparative Example 4, the pencil hardness of the resin film 31 is much higher than that of Example 3, which may have an effect. In other words, it is considered that the resin film 31 that is too strong may hinder the sliding of the alkaline soap layer 31A.
[0211] (Comparative Example 5)
[0212] Comparative Example 5 is an example in which the pencil hardness of the resin film 31 is high. Comparative Example 5 achieves a pencil hardness of 3H by using a fluororesin different from that of Example 5. The SP value of Comparative Example 5 is 6.7 cal / cm 3 , which is very low as in Example 5, but the number of tightening and loosening is only 4. It can be seen from this that if the pencil hardness of the resin film 31 is not suppressed to a low level, the lubricating effect of the alkaline soap layer 31A cannot be fully obtained. Based on the results of Example 5, it is considered that the pencil hardness is preferably F or less.
[0213] The entire contents of Japanese Patent Application No. 2022-134377 (filed on August 25, 2022) to which this application claims priority are incorporated herein by reference. Although the invention is described with reference to a limited number of embodiments, the scope of the invention is not limited thereto, and changes based on the embodiments disclosed above are obvious to those skilled in the art.
[0214] Explanation of symbols
[0215] 1 Pin
[0216] 1a External thread
[0217] 2 Sleeve (coupling)
[0218] 2a Internal thread
[0219] 3 Heavy Hammer
[0220] 3A Heavy hammer body
[0221] 4 Power tongs
[0222] 12 Penetration rod
[0223] 13 Insertion rod
[0224] 20 Suspension device (crane)
[0225] 21 Chain (sling)
[0226] 30 Other solid lubricating films
[0227] 31 Resin film
[0228] 31A Alkaline soap layer
Claims
1. An oil well pipe, which is used for an oil well pipe threaded joint formed by connecting a sleeve with an internal thread and a pin with an external thread, and is an oil well pipe constituting the sleeve or the pin, wherein: The outermost layer of the threaded portion has a resin coating containing an alkaline soap as a solid lubricant in a binder resin. The resin film has an alkaline soap layer formed on the surface.
2. The oil well pipe according to claim 1, wherein: The alkaline soap contained in the resin film is concentrated on the surface side to form the alkaline soap layer.
3. The oil well pipe according to claim 1 or claim 2, wherein: The SP value of the binder resin is 10.0 cal / cm 3 the following.
4. The oil country pipe according to any one of claims 1 to 3, wherein: The weight of the alkaline soap is 0.01 times or more and 3 times or less the weight of the binder resin.
5. The oil country pipe according to any one of claims 1 to 4, wherein: The resin film has a pencil hardness of F or less.
6. The oil country pipe according to any one of claims 1 to 5, wherein A separate solid lubricating film is provided as a lower layer of the resin film.
7. An oil well pipe threaded joint, which is formed by connecting a sleeve with an internal thread and a pin with an external thread, wherein: At least one of the sleeve and the pin is formed of the oil country tubular good according to any one of claims 1 to 6.
8. A coating material for forming the outermost layer on the threaded portion of an oil well pipe, wherein: Contains solvent, binder resin and solid lubricant, As the solid lubricant, an alkaline soap is included. The SP value of the binder resin is 10.0 cal / cm 3 The average molecular weight is 10000 or more and 300000 or less, The weight of the alkaline soap is 0.01 times or more and 3 times or less the weight of the binder resin.
Citation Information
Patent Citations
Composition for forming lubricating film suitable for lubrication treatment of screw joint
JP2002173692A
Threaded joints for steel pipes
JP2008537062A
Dry wire drawing lubricant
JP2009132811A
Tubular threaded joint excellent in high torque performance
JP2013108556A
Steel wire excellent in corrosion resistance and appearance after working
JP2017066515A